Mapping The Impact Of Digital Marketing Strategies On Customer Loyalty: A Systematic Review And Bibliometric Synthesis - Wiwin Riski Windarsari (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
Customer loyalty is a key determinant of business sustainability in the digital era, yet the effectiveness of different digital marketing strategies remains fragmented across industries. This study aims to identify the most effective digital marketing strategies for enhancing customer loyalty during 2015–2025. A systematic literature mapping combined with thematic and bibliometric analysis was conducted on 11 empirical studies that examined the link between digital strategies and loyalty dimensions (cognitive, affective, conative, and behavioral). The results show that interactive and personalized strategies such as social media marketing, e-CRM, chatbots, and multi-channel integration demonstrate the strongest influence on loyalty. Trust, customer engagement, and satisfaction consistently emerged as mediating factors that reinforce these effects across diverse sectors, including banking, hospitality, fashion, e-commerce, and retail. Effective digital strategies should prioritize interactivity, personalization, and relationship-building rather than one-way information delivery. Their success depends not only on technological features but also on shaping trust and emotional connections with customers. This study contributes by synthesizing cross-industry evidence through a combined systematic, thematic, and bibliometric approach. It advances the state of the art by clarifying which strategies are most impactful and highlighting key mediators, providing both theoretical insight and practical guidance for marketers and researchers in designing loyalty-oriented digital strategies.